The Future Role of the Euro - Jakob De Vries (European Political Economy Review, 2005)
Although the euro has stimulated European financial markets by lowering the barriers to cross-border transactions, thus encouraging the emergence of a money market and a pan-European private bond market; the euro-denominated asset market is far from the existing types of international markets for the dollar. In the world currency markets, the emergence of the euro has not changed the relative position of the old European currencies vis-à-vis the dollar and the yen. And the shares in the official reserves of Central Banks also remained stable. In the future, three questions arise, which this article tries to answer: Do Europeans want the euro to become an international currency? Is the euro able to occupy such a position?If the euro could acquire an international status, would this contribute to improving the stability of the international monetary system?
Keywords: F33; 330; Euro